Analisis Perbedaan Abnormal Return, Market Capitalization Dan Security Return Variability Pada Saham LQ45 Sebelum Dan Setelah Pengumuman Kasus Pertama Covid-19 Terkonfirmasi Di Indonesia - Ni Kadek Aprina Asriani; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the difference between the average abnormal return, the average market capitalization and the average security return variability on the LQ45 index stock before and after the announcement of the first confirmed case of Covid-19 in Indonesia. Sources of data in this study using secondary data sourced and obtained through the website www.idx.com and www.finance.yahoo.com. The population is all issuers listed in the LQ45 stock index members on the IDX with the sample selection method, namely the purposive sampling method. The period of this research is 6 days. Hypothesis testing using the Wilcoxon Signed Ranks test. The results of this study are that there are no differences in abnormal returns before and after the announcement of the first confirmed case of COVID-19 in Indonesia, but there are differences in market capitalization and security return variability before and after the announcement of the first confirmed case of COVID-19 in Indonesia. Keyword: Covid-19, Abnormal Return, Market Capitalization, Security Return Variability.